DISCURSO DE CRIANÇAS: UMA METODOLOGIA POUCO UTILIZADA - da Costa Brito, Clecina; Jossany Almeida Brito, Mayra; Pereira de Oliveira, Rosivaldo; Ferreira Lima, Edmar; Cristhina Aragão Pereira, Cynara (Revista Form@re - Parfor/UFPI, 2026)
.